Traveling Ultralow‐Frequency Waves and Their Influences Over Low‐Energy, Charged Particles. Issue 5 (27th May 2018) - Yang, Mu; Zhou, Xu‐Zhi; Zong, Qiu‐Gang; Zhang, Long‐Fei; Rankin, Robert; Wang, Yong‐Fu
Abstract: In Earth's magnetosphere, the behavior of charged particles in response to ultralow‐frequency (ULF) waves has long been understood in the framework of their resonant interactions with standing hydromagnetic waves. It has been argued that for impulse‐excited waves, it may take a few wave cycles for the standing structure to be fully established; during these initial cycles, the waves should propagate along magnetic field lines before they are reflected from the ionosphere and are superimposed to form standing waves. However, it has been unclear how particles behave during the initial, traveling stage of the ULF wave evolution. Here we use a simplistic model of ULF wave evolution from traveling to standing waves, to investigate the response of low‐energy electrons (presumably of plasmaspheric and/or ionospheric origin) immediately after the wave excitation. We find that an off‐equatorial spacecraft would observe dispersive signatures in both energy and pitch angle spectra of electron fluxes, and the flux modulation may appear (at specific pitch angle and energy ranges) prior to the electromagnetic oscillations. These predicted signatures, consistent with the scenario of field‐aligned streaming electrons surfing on traveling ULF waves, are indeed observed by the Cluster spacecraft during an ULF wave event on 25 September 2001. Our identification of such signatures, therefore, provides a new understanding of ULF wave evolution and wave‐particle interactions in the inner magnetosphere. Key Points: Ultralow‐frequency (ULF) waves may initially travel along geomagnetic field lines before their transition to standing hydromagnetic waves Charged particles may interact with traveling waves during their bounce motion and possibly experience a surfratron‐type acceleration The wave‐particle interaction explains the observations of dispersive signatures, in the energy and pitch angle spectra of particle fluxes